I'm stuck on a question on Binomial Expressions.. any help? c:

Lexadis

New member
Joined
Mar 22, 2013
Messages
17
Solved://I'm stuck on a question on Binomial Expressions.. any help? c:

So currently we are studying expressions based on (x+b)3 and (x-b)3.
.
In this aspect, there's this question..
Q. Obtain the expression of (x-y)3, by substituting (-y) for y in the expansion of (x+y)3.

So.. I tried several ways, and I hope the second method is correct, but I just wanted to be sure ;D

Method I
I tried expanding it instead of using the formula, and got stuck in half :/
(x+y)3 = (x+y) (x+y)2
= (x-y) (x-y)2
= (x-y) (x2-2xy+y2)
= x(x2-2xy+y2) - y(x2-2xy+y2)
= x3 - 2x2y + xy2 - x2y + 2xy2 - y3
= x3 - 3x2y + 3xy2 - y3
=?
I know that this is the equation which finally builds upto (x-y)3, but I just don't know how to reconstruct it back :sad:
Method II
And here again I tried expanding directly through the formula, and got stuck in the same place:
(x+y)3 = x3 + 3x2y + 3xy2 + y3
= x3 + 3x2(-y) + 3x(-y)2 + (-y3)
= x3 - 3x2y + 3xy2 - y3
= ?

So.. I tried solving after this, but it got me wrong. Here's my result:
= x3 - 3x2y + 3xy2 - y3

= x2 (x-3y) - y2 (y-3x)
= (x-y)2(x-3y)(y-3x)
= (x-y)(x+y)(x-3y)(y-3x)
= ?

Any help appreciated. Thank you c:
 
Last edited:
So currently we are studying expressions based on (x+b)3 and (x-b)3.
.
In this aspect, there's this question..
Q. Obtain the expression of (x-y)3, by substituting (-y) for y in the expansion of (x+y)3.

So.. I tried several ways, and I hope the second method is correct, but I just wanted to be sure ;D

Method I
I tried expanding it instead of using the formula, and got stuck in half :/
(x+y)3 = (x+y) (x+y)2
(x-y)³ = (x-y) (x-y)2
= (x-y) (x2-2xy+y2)
= x(x2-2xy+y2) - y(x2-2xy+y2)
= x3 - 2x2y + xy2 - x2y + 2xy2 - y3
= x3 - 3x2y + 3xy2 - y3
= the correct answer!
I know that this is the equation which finally builds upto (x-y)3, but I just don't know how to reconstruct it back :sad:
Method II
And here again I tried expanding directly through the formula, and got stuck in the same place:
(x+y)3 = x3 + 3x2y + 3xy2 + y3
(x-y)³ = x3 + 3x2(-y) + 3x(-y)2 + (-y3)
= x3 - 3x2y + 3xy2 - y3
= the correct answer!

So.. I tried solving after this, but it got me wrong. Here's my result:
= x3 - 3x2y + 3xy2 - y3

= x2 (x-3y) - y2 (y-3x)
= (x-y)2(x-3y)(y-3x) NO
= (x-y)(x+y)(x-3y)(y-3x)
= ?

Any help appreciated. Thank you c:
You did it right two times! If you want to factor the result, try dividing by (x-y).
 
You did it right two times! If you want to factor the result, try dividing by (x-y).
I'm still finding it unable to do it :/ The fact is, we have to get (x-y)3 from x3 - 3x2y + 3xy2 - y3.
So I tried factorizing, as you stated, by (x-y) and I just can't do it >.> Anyways, this was what I tried:
x3 - 3x2y + 3xy2 - y3
=x2(x-3y) + y2 (3x-y)
=(x+y)2(x-3y)(3x-y)
=(x+y)2(x-y)(3x-3)
=?

I'm not sure of how to facorize them by (x-y) either. Any help? Thank you very much c:

---edit---
I tried another method, but I didn't get the answer I needed. But still, I got a completely different one. So here it goes:
x3 - 3x2y + 3xy2 - y3
=x2(x-3y) + y2 (3x-y)
=(x+y)2(x-3y)(3x-y)
= x2 + 2xy + y2 + 3x2 - 10xy + 3y2 [I expanded (x+y)2, as well as (x-y)(3x-3)]
= 4x2 - 8xy + 4y2
= 4 (x2 - 2xy + y2)
= 4 [x(x-y)-y(x-y)]
= 4(x-y)(x-y)
=4 (x-y)2
= ?
I have to get (x-y)3 as the end result, but I seem to have ended up getting something else :confused: Any help as to where I have gone wrong is appreciated, Thank you. c:
 
Last edited:
The fact is, we have to get (x-y)3 from x3 - 3x2y + 3xy2 - y3.

x3 - 3x2y + 3xy2 - y3

= x3 - 2x2y + xy2 -x2y + 2xy2 - y3

= x(x2 - 2xy + y2) - y(x2 - 2xy + y2)

Can you go from here....
 
I'm still finding it unable to do it :/ The fact is, we have to get (x-y)3 from x3 - 3x2y + 3xy2 - y3.
Having found the expansion of (x-3)³ by substituting -y for y in the expansion of (x+y)³, namely doing your Method II, write down all the steps from your Method I, IN REVERSE ORDER.
(x-y)3 = (x-y) (x-y)2
= (x-y) (x2-2xy+y2)
= x(x2-2xy+y2) - y(x2-2xy+y2)
= x3 - 2x2y + xy2 - x2y + 2xy2 - y3
= x3 - 3x2y + 3xy2 - y3
x3 - 3x2y + 3xy2 - y3
= x3 - 2x2y + xy2 - x2y + 2xy2 - y3
= x(x2-2xy+y2) - y(x2-2xy+y2)
= (x-y) (x2-2xy+y2)
= (x-y) (x-y)²
= (x-y)³
 
Top